Analytic Calibration in Andreasen‐Huge SABR Model. Issue 114 (22nd July 2021) - Feldman, Konstantin
Abstract : We derive analytic formulae which link alpha, nu and rho parameters in Andreasen‐Huge‐style SABR model to the ATM price and option prices at four strikes close to ATM. Based on these formulae we give a characterization for the SABR parameters in terms of derivatives of the swap rate forward probability density function. We test the analytic result in the application to the interest rate futures option market.